2018
DOI: 10.1007/s00122-018-3061-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new GmFAD3A allele in Brazilian CS303TNKCA soybean cultivar

Abstract: We molecularly characterized a new mutation in the GmFAD3A gene associated with low linolenic content in the Brazilian soybean cultivar CS303TNKCA and developed a molecular marker to select this mutation. Soybean is one of the most important crops cultivated worldwide. Soybean oil has 13% palmitic acid, 4% stearic acid, 20% oleic acid, 55% linoleic acid and 8% linolenic acid. Breeding programs are developing varieties with high oleic and low polyunsaturated fatty acids (linoleic and linolenic) to improve the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Genes controlling the oleic acid and PUFA contents in soybean seed oil have been characterized, containing the two oleate desaturase genes GmFAD2-1A and GmFAD2-1B and three linoleate desaturase genes GmFAD3A, GmFAD3B, and GmFAD3C [11,12]. Mutation of GmFAD3 resulted in lower linolenic acid content (from 7% to 10%) [10,13]. A tobacco FAD3 expressed in rice could increase α-linolenic acid (ALA, C18:3) level up to 2.5-fold [14].…”
Section: Introductionmentioning
confidence: 99%
“…Genes controlling the oleic acid and PUFA contents in soybean seed oil have been characterized, containing the two oleate desaturase genes GmFAD2-1A and GmFAD2-1B and three linoleate desaturase genes GmFAD3A, GmFAD3B, and GmFAD3C [11,12]. Mutation of GmFAD3 resulted in lower linolenic acid content (from 7% to 10%) [10,13]. A tobacco FAD3 expressed in rice could increase α-linolenic acid (ALA, C18:3) level up to 2.5-fold [14].…”
Section: Introductionmentioning
confidence: 99%
“…FAD3 genes are responsible for the conversion of LA into ALA in the fatty acid biosynthetic pathway. Previous studies have supported the role of FAD3 genes in ALA concentration via the discovery of mutant alleles of FAD3 genes that reduce levels of ALA for new genetic resources for soybean. The combination of fad3a and either fad3b ( Glyma.02g227200 ) or fad3c ( Glyma.18g062000 ) leads to ∼3% ALA in soybean oil. Soybean lines with 1% ALA were developed using the combination of all three FAD3 mutant alleles . In addition, expression levels of FAD3A are significantly higher than those of FAD3B and FAD3C in the developing seed stages .…”
Section: Discussionmentioning
confidence: 99%
“…Novel genetic resources selected from natural variations or induced by chemical mutagenesis have been used previously to alter fatty acid profiles in soybean breeding programs. The benefit of mutation breeding is that changes induced by mutagens are stable and heritable to subsequent generations. Chemical mutagenesis has been successfully used to generate novel genetic diversity in soybean. , Our previous study revealed that ethyl methanesulfonate (EMS) mutagenesis of a soybean cultivar, Pungsannamul, resulted in a soybean mutant line, PE2166, with an elevated concentration of ALA fatty acid .…”
Section: Introductionmentioning
confidence: 99%
“…Within the soybean genome, four GmFAD3 genes have been previously identified as GmFAD3A (Glyma.14g194300), GmFAD3B (Glyma.02g227200), GmFAD3C (Glyma.18g062000), and GmFAD3D (Glyma.11g174100) [ 27 , 28 ]. A series of novel allelic variations in GmFAD3A have been reported as a source that reduces linolenic acid content [ 29 , 30 ]. Reinprecht et al [ 31 ] isolated a low linolenic acid mutant line (RG10) resulting in a truncated GmFAD3A protein and a splicing mutation at the GmFAD3B.…”
Section: Introductionmentioning
confidence: 99%